A prospective study on cancer risk after total hip replacements for 41,402 patients linked to the Cancer registry of Norway - Eva Dybvik; Ove Furnes; Leif I. Havelin; Sophie D. Fosså; Clement Trovik; Stein Atle Lie (BMC Musculoskeletal Disorders, 2020)
Abstract Background Concerns have been raised that implants used in total hip replacements (THR) could lead to increased cancer risk. Several different materials, metals and fixation techniques are used in joint prostheses and different types of articulation can cause an increased invasion of particles or ions into the human body. Methods Patients with THR registered in the Norwegian Arthroplasty Register during 1987–2009 were linked to the Cancer registry of Norway. Patients with THR due to osteoarthritis, under the age of 75 at time of surgery, were included. Standardized incidence ratios (SIR) were applied to compare cancer risk for THR patients to the general population. Types of THR were divided into cemented (both components), uncemented (both components), and hybrid (cemented femoral and uncemented acetabular components). To account for selection mechanisms, time dependent covariates were applied in Cox-regression, adjusting for cancer risk the first 10 years after surgery. The analyses were adjusted for age, gender and if the patient had additional THR-surgery in the same or the opposite hip. The study follows the STROBE guidelines. Results Comparing patients with THR to the general population in Norway we found no differences in cancer risk. The overall SIR for the THR-patients after 10 years follow-up was 1.02 (95% CI: 0.97–1.07). For cemented THR, the SIR after 10 years follow-up was 0.99 (95% CI: 0.94–1.05), for uncemented, 1.16 (95% CI: 1.02–1.30), and for hybrid 1.12 (95% CI: 0.91–1.33). Adjusted Cox analyses showed that patients with uncemented THRs had an elevated risk for cancer (hazard ratio: HR = 1.24, 95% CI: 1.05–1.46, p = 0.009) when compared to patients with cemented THRs after 10 years follow-up. Stratified by gender the increased risk was only present for men. The risk for patients with hybrid THRs was not significantly increased (HR = 1.07, 95% CI: 0.85–1.35, p = 0.55) compared to patients with cemented THRs. Conclusions THR patients had no increased risk for cancer compared to the general population. We found, however, that receiving an uncemented THR was associated with a small increased risk for cancer compared to cemented THR in males, but that this may be prone to unmeasured confounding.